The effect of caffeine, nap opportunity and their combination on biomarkers of muscle damage and antioxidant defence during repeated sprint exercise - Mohamed Romdhani; Nizar Souissi; Ismail Dergaa; Imen Moussa-Chamari; Yassine Chaabouni; Kacem Mahdouani; Olfa Abene; Tarak Driss; Karim Chamari; Omar Hammouda (Termedia Publishing House, 2021)
To investigate the effect of 20 min nap opportunity (N20), 5 mg · kg -1 of caffeine (CAF) and their combination (CAF+N20) on the biochemical response (energetic biomarkers, biomarkers of muscle damage and enzymatic antioxidants) to the running-based anaerobic sprint test. Fourteen highly trained male athletes completed in a double-blind, counterbalanced and randomized order four test sessions: no nap with placebo (PLA), N20, CAF and CAF+N20. Compared to PLA, all treatments enhanced maximum and mean powers. Minimum power was higher [(mean difference) 58.6 (95% confidence interval = 1.31-116) Watts] after CAF and [102 (29.9-175) Watts] after CAF+N20 compared to N20. Also, plasma glucose was higher after CAF [0.81 (0.18-1.45) mmol·l -1 ] and CAF+N20 [1.03 (0.39-1.64) mmol·l -1 ] compared to N20. However, plasma lactate was higher [1.64 (0.23-3.03) mmol ·l -1 ] only after N20 compared to pre-exercise, suggesting a higher anaerobic glycolysis during N20 compared to PLA, CAF and CAF+N20. Caffeine ingestion increased post-exercise creatine kinase with [54.3 (16.7-91.1) IU·l -1 ] or without napping [58.9 (21.3-96.5) IU·l -1 ] compared to PLA. However, superoxide dismutase was higher after napping with [339 (123-554) U·gHB -1 ] or without caffeine [410 (195-625) U·gHB -1] compared to PLA. Probably because of the higher aerobic glycolysis contribution in energy synthesis, caffeine ingestion resulted in better repeated sprint performance during CAF and CAF+N20 sessions compared to N20 and PLA. Caffeine ingestion resulted in higher muscle damage, and the short nap enhanced antioxidant defence with or without caffeine ingestion.